Shock Wave Diffraction around Circular Cylinder Using Unstructured Adaptive Meshes - SUZUKI, Yujiro; NAKAKURA, Yasuki; TANAHASHI, Takahiko; ITO, Akishige (Nihon Kikai Gakkai rombunshuu. B hen, 1997)
The study of flow around a circular cylinder is one of the most important problems in not only basic research but also analysis of a complexity object. No numerical simulation of shock wave diffraction around circular cylinder has been carried out thus far. Under supersonic flow in particular, the numerical result is insufficient for the lack of resolution in the complicated flow around passing through circular cylinder. Therefore, we used unstructured adaptive meshes which can automatically divide elements only in the region of large variation. In the present paper, unstructured adaptive meshes were applied to MUSCL (monotone upstream centered scheme for conservation laws). Shocked flows around circular cylinder were investigated using the scheme. The reflection process was analyzed from the numerical results. The effects of limiter function were examined.